Cardiac conduction abnormalities preceding transoesophageal echocardiographic evidence of perivalvar extension of infection in a case of salmonella prosthetic valve endocarditis. Issue 4 (1st October 1997) - Miyamoto, Michael I; Hutter, Adolph M; Blum, Jonathan H; Torchiana, David F
Abstract : A 59 year old African-American man developed complete heart block in association with Salmonella enteritidis prosthetic valve endocarditis. Severe cardiac conduction abnormalities signalled the presence of perivalvar extension of infection before development of evidence of abscess by transoesophageal echocardiography. Cardiac conduction temporarily returned after debridement and aortic homograft placement. This case emphasises the value of electrocardiographic monitoring in the detection of perivalvar extension of infection complicating infective endocarditis, even in the era of sophisticated imaging modalities.